Wakaf in Malaysia: It legal history - Md Dahlan, Nuarrual Hilal (2003)
Islamic laws had existed and were well entrenched in the Malay archipelagos since the coming of Islam in the 13th century.A rock inscripted in Jawi (the indigenous Malay's version of the Arabic writings) found at an adjacent village (Kampung Buluh at Sungai Teresat, Terengganu), dated 1302 AD or 702 AH is proof to these facts. Since the 13th century, it is believed that Islamic laws had already played a comprehensive part in the administration of the local communities' criminal justice system such as in family law, criminal law, and land law, and included as well the procedural laws and the law of evidence.This can be further be proven and buttressed by the laws that were adopted and practiced in the several states that comprised Malaya such as Melaka, Pahang, Kedah, Johore and Perak in the 13th, 14th, 15th, 16th, 17th and 18th centuries before the colonialist's master in the late 18" century and onwards began to meddle with the local laws.The British gradually introduced her English laws and equity, first through the charter of justices in Penang, Melaka and Singapore, and later through the enactment of civil law ordinances in the Malay states, in Sabah and Sarawak, as well in the early 191h century.The onslaught of English laws and equity by the colonial master had the effect of marginalising Islamic laws, and hitherto, through the passage 01 time, Islamic laws then became the secondary laws in the Malaya. Islamic law being the law of the land in Malaya is never disputed.This was illustrated in the case of Ramah v Laton where the English judge did not allow an expert to give evidence on it as it not a foreign law.In Islamic matters relating to wakaf, which means 'detention' and connotes the tying up of property in perpetuity for the benefit of the public, its application in Malaysia (then it was Malaya) was no less significant. According to an Islamic jurist, wakaf is the detention of a thing in the implied ownership of Almighty God, in such a way that its profits may be applied for the benefit of human beings. The moment it has been done, the detention then becomes absolute, so that the thing dedicated can neither be sold, given, nor inherited.According to some historical researchers,the implementation of wakaf in the Malay archipelagos commenced contemporaneously with the conversion of the locals into Islam. Ironically, there are little available records to highlight on the administration and management of wakaf.Such records indicated that the settlers administered the administration of this trusts personally or by the society leaders of the particular communities at that time such as the ham (head of the mosque), Bilal (deputy of the mosque) or Penghulu (the Head of a village or settlement).Most disputes, which arose were settled and resolved by the Islamic scholars at that time without letting the parties having to resort to a courts' trial.The first recorded case involving wakaf was Ashhee & Ors v. Sved Abu Bakar (1985) 4 Kv 213(check the citation).The civil court in this case had decided that the applicable law in resolving disputes involving wakaf is English law. Subsequent cases too upheld similar findings.However, 100 years after the abovementioned case, the civil courts began to decide otherwise.in that only Islamic law is the applicable law to resolve disputes in wakaf. Several cases were likewise decided such as Commissioner of Religious Affairs, Trenggganu v. Tengku Mariam, Tengku Embong v. Tengku Maimunah, Tengku Abdul Kadir bin Tengku Chik & Anor v. Majlis Agama Islam, Kelantan, Re Dato Bentara Luar, Mailis Agama Islam Pulau Pinang v. Isa Abdd Rahmah & Anor, G Rethinasamy v. Mailis Agama Islam Pulau Pinang & Anor, Shaik Zolkafily bin Shaik Natar & Ors (sued as trustees of the estate of Sheik Eusoff bin Sheik Latiff deceased) v. Majlis Agama Islam Pulau Pinang dan Seberang Perai.Albeit after 100 years from the decision of Ashbee, thc civil courts have taken the bold and firm decision thai only Islamic Law is the law applicable to settle disputes concerning wakaf, yet the jurisdiction to hear and determine wakaf is still in the hands of the civil courts, not the syariah courts.The Malaysian Federal Constitution pursuant to List II of the 9th Schedule and pursuant to the provisions in the respective states' enactments on the administration of Islamic law, provide that wakaf shall be within the jurisdiction of the syariah court.Alas, this has been decided otherwise, and negated by the civil courts.Based on the cases decided, even though the jurisdiction to hear wakaf exclusively falls within the jurisdiction of the syariah court, yet the civil court vehemently decided that to be in their domain. This paper intends to study cases involving wakaf so as to give suggestions and solutions in the problems on this conflict of jurisdiction to hear wakaf between civil courts and the syariah courts in Malaysia. It is hoped that through the illumination of this paper on the legal history of wakaf and its conflict of jurisdiction between the civil court and the syariah court in Malaysia, will give us some insights how the institution of wakaf could be resolved.